ANALISIS KERJASAMA ORANG TUA DAN GURU DALAM PEMBENTUKAN KARAKTER SISWA PADA MATA PELAJARAN AKIDAH AHLAK KELAS VIIIᴬ DI MTs N 2 KUANTAN SINGINGI - Uci Romadayani; Zulhaini Zulhaini; Helbi Akbar (Universitas Islam Kuantan Singingi, 2023)
The background of this research is the concern, responsibility, religiosity and honesty of students at this time has decreased this can be seen from the presence of students who come late, do not comply with school rules, do not go to school and cheat.The purpose of this study was to find out how the form of collaboration between parents and teachers in the formation of students' character in the Akhalak Akidah Subject Class VIIIᴬ at MTs N 2 Kuantan Singingi. research is qualitative, the sample in this study was 32 students of class VIIIA and 1 teacher of aqidah ahlak, data collection used observation, interviews, and documentation techniques. The involvement of parents in schools will ease teachers in fostering children's self-confidence, reduce student discipline problems and increase children's motivation. Based on the results of data analysis that researchers have done, the equations used are: P100 = = P 100= = P100=4,8% students 3.9 there are 1 person with a percentage of 4.8%. The involvement of parents in schools will ease teachers in fostering children's self-confidence, reduce student discipline problems and increase children's motivation. It can be seen from the character value of parents whose character value is 98, there is 1 person with a percentage of 4.8% and so is the involvement of teachers whose character value is 3.8, there is one person with a percentage of 4.8%. So the collaboration between parents and teachers at MTs N 2 Kuantan Singingi is always carried out, namely, a meeting between parents and the school every 1 time at the beginning of the semester, in the meeting many things are discussed including student discipline, student assignments during the process teaching and learning and special meetings with parents/guardians of students with cases